Integrated auditory-vocal embodied training for expressive authentic intonation in Chinese zither performance - Jiang, He; Lu, Hui (Frontiers in Neuroscience, 2025)
BackgroundChinese zither music relies on culturally specific microtones (e. g., FA+ and TI–) that differ from Western equal temperament, yet prolonged exposure to standardized tuning often leads to the erosion of these traditional intonation practices. While embodied cognition theory emphasizes the role of sensorimotor integration in learning, its application to the acquisition of non-fixed pitch systems in intangible cultural heritage music remains underexplored.ObjectiveThis study aimed to examine whether a structured auditory-vocal embodied training protocol—integrating listening, vocal imitation, and metaphoric gestures—could enhance zither learners' accuracy in producing traditional microtones, and to provide empirical evidence for the effectiveness of embodied cognition theory in sustaining culturally authentic musical intonation.MethodsA quasi-experimental design was employed with 63 intermediate-level zither students. Participants were assigned to an experimental group, which completed a 1-week auditory-vocal-gestural training program, or a control group, which continued regular practice without multimodal integration. Pitch accuracy on two critical tones (FA+ and TI–) was assessed through pre- and post-tests.ResultsThe experimental group demonstrated significantly greater improvement in Chinese-style pitch accuracy compared to the control group, along with a marked shift in intonation perception away from equal-tempered biases.ConclusionThe findings indicate that multisensory embodied training, grounded in the principles of perceptual-motor coupling and gestural simulation, effectively promotes the internalization of traditional microtonal intonation. This study not only offers a novel pedagogical approach for preserving intangible cultural heritage in music education but also substantiates the role of embodied cognition in acquiring culturally situated sensorimotor skills.